2019
DOI: 10.1111/tpj.14326
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive phenotyping reveals interactions and functions of Arabidopsis thaliana TCP genes in yield determination

Abstract: Summary Members of the Arabidopsis thaliana TCP transcription factor (TF) family affect plant growth and development. We systematically quantified the effect of mutagenizing single or multiple TCP TFs and how altered vegetative growth or branching influences final seed yield. We monitored rosette growth over time and branching patterns and seed yield characteristics at the end of the lifecycle. Subsequently, an approach was developed to disentangle vegetative growth and to determine possible effects on seed yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…The dynamic growth patterns were observed in Arabidopsis day and night ( Wiese et al, 2007 ; van Es et al, 2019 ) and demonstrated that daylight growth was responsible for 70% of growth activities ( Wiese et al, 2007 ). The overall growth pattern of the selected plant showed a somewhat linear trend for multiple growth stages ( Figure 2B ) and agreed well with previous studies on Arabidopsis ( van Es et al, 2019 ). Three of 122 plant samples were selected and the dynamic growth pattern of the individual plants was compared ( Figure 2C ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The dynamic growth patterns were observed in Arabidopsis day and night ( Wiese et al, 2007 ; van Es et al, 2019 ) and demonstrated that daylight growth was responsible for 70% of growth activities ( Wiese et al, 2007 ). The overall growth pattern of the selected plant showed a somewhat linear trend for multiple growth stages ( Figure 2B ) and agreed well with previous studies on Arabidopsis ( van Es et al, 2019 ). Three of 122 plant samples were selected and the dynamic growth pattern of the individual plants was compared ( Figure 2C ).…”
Section: Resultsmentioning
confidence: 99%
“…Arabidopsis thaliana was selected because it is a model plant for scientists and is rich in several noteworthy information. Moreover, the growth pattern of the gene function ( van Es et al, 2019 ) and stress responses ( Dhondt et al, 2014 ) was analyzed using time series.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The activity of Arabidopsis thaliana gene promoters was predicted using ML, based on the presence of cis-regulatory elements (Uygun et al, 2019). Related to this, (Washburn et al, 2019) applied DL to predict maize gene expression levels.…”
Section: Ll Open Accessmentioning
confidence: 99%
“…As illustrated in Figure 3 , the different macroscopic levels can be studied using different imaging systems. Development at the level of plant organs can be studied in detail using microscope setups ( Dhondt et al., 2013 ), growth of the full plant can be phenotyped in growth chambers ( van Es et al, 2019 ) or using robotic devices in greenhouses and open fields, e.g ( van der Heijden et al, 2012 ; Virlet et al, 2017 ), and drones can be used to inspect plots or complete fields, e.g ( Araus et al., 2018 ). Different imaging sensors exist, measuring different parts of the electromagnetic spectrum, such as red-green-blue color, multispectral and hyperspectral, long-wave infrared (thermal), chlorophyll-fluorescence, and tomography (magenetic resonance imaging [MRI], positron emission tomography [PET], computerized tomography [CT]) ( Li et al., 2014 ).…”
Section: Machine Learning For Macroscopic Phenotypesmentioning
confidence: 99%